2020
DOI: 10.1590/2237-6089-2019-0016
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of mindfulness-based cognitive therapy for reducing rumination and improving mindfulness and self-compassion in patients with treatment-resistant depression

Abstract: Introduction: Depression is one of the most important psychiatric disorders, and the rate of recurrence is high. The heavy cost burden of depression is probably due to treatment-resistant depression. The purpose of this study was to determine the effectiveness of mindfulness-based cognitive therapy (MBCT) in patients with treatment-resistant depression (TRD). Method: The present study was a quasi-experimental study conducted with twenty-four patients with treatment-resistant depression. Participants were selec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 42 publications
0
19
0
Order By: Relevance
“…Some studies had monitored 45 participants for 42 days on the mindfulness intervention 10.3389/fpsyg.2022.987537 process, and it was found that the degree of ruminative thinking decreased significantly after 1 week and 1 month (Andreotti et al, 2018). Experimental research has been conducted and found that mindfulness cognitive therapy reduces depression and ruminative thinking in the experimental group (Foroughi et al, 2020). Mindfulness cognitive therapy encourages people under depression to observe their thoughts and feelings without judgment.…”
Section: The Chain Intermediary Role Of Mindfulness and Ruminative Th...mentioning
confidence: 99%
“…Some studies had monitored 45 participants for 42 days on the mindfulness intervention 10.3389/fpsyg.2022.987537 process, and it was found that the degree of ruminative thinking decreased significantly after 1 week and 1 month (Andreotti et al, 2018). Experimental research has been conducted and found that mindfulness cognitive therapy reduces depression and ruminative thinking in the experimental group (Foroughi et al, 2020). Mindfulness cognitive therapy encourages people under depression to observe their thoughts and feelings without judgment.…”
Section: The Chain Intermediary Role Of Mindfulness and Ruminative Th...mentioning
confidence: 99%
“…MT might facilitate the identification of ruminative patterns, understanding the consequences of these kinds of thoughts and taking constructive steps to reduce mental distress (Smart et al, 2016). Exploratory studies have observed that MT aimed at reducing ruminative thinking in depressive patients also improves mediators such as mindfulness and self-compassion, although more research to establish the specific causal links between these two groups of variables is needed (Foroughi et al, 2020; Frostadottir & Dorjee, 2019). These indirect effects of mindfulness practice have been observed in clinical samples using instructor-led MT, but they have not been studied in secondary teachers using self-taught MT.…”
Section: Instructor-led and Self-taught Mt For Enhancing Teacher Well...mentioning
confidence: 99%
“…The 19 studies [ 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 ] included were all focused on MBIs, and the specific intervention programs were diversified in terms of group intervention. Females made up more than 50% of all the studies.…”
Section: Resultsmentioning
confidence: 99%
“…Three studies reported on placebo control, including relaxation [ 31 ], pill placebo [ 34 ], and psychology education [ 37 ]. Eleven studies used blank controls (BCs), including waiting lists [ 30 , 33 , 36 , 40 , 47 , 48 ] and treat-as-usual methods [ 32 , 38 , 42 , 43 , 44 ]. Five articles reported follow-up data with a follow-up period of 1–6 months.…”
Section: Resultsmentioning
confidence: 99%